Broadband Near-Infrared Absorber Based on All Metallic Metasurface - Zhang, Ke (Materials (Basel), 2019)
Perfect broadband absorbers have increasingly been considered as important components for controllable thermal emission, energy harvesting, modulators, etc. However, perfect absorbers which can operate over a wide optical regime is still a big challenge to achieve. Here, we propose and numerically investigate a perfect broadband near-infrared absorber based on periodic array of four isosceles trapezoid prism (FITP) unit cell made of titanium (Ti) over a continuous silver film. The structure operates with low quality (Q) factor of the localized surface plasmon resonance (LSPR) because of the intrinsic high loss, which is the foundation of the broadband absorption. The high absorption of metal nanostructures mainly comes from the power loss caused by the continuous electron transition excited by the incident light inside the metal, and the resistance loss depends on the enhanced localized electric field caused by the FITP structure. Under normal incidence, the simulated absorption is over 90% in the spectrum ranging from 895 nm to 2269 nm. The absorber is polarization-independent at normal incidence, and has more than 80% high absorption persisting up to the incident angle of ~45° at TM polarization.